Characteristics of Mythological Worlds and their Impact on Human Consciousness (Zien Journal of Social Sciences and Humanities, 2022)
This article discusses myth and its types, mythology and its images, and discusses the scholar's scientific basis. The study presents mythological ideas and philosophical views on the impact of worldviews on the universe and the human mind.